Super‐beacons: Open‐source probes with spontaneous tuneable blinking compatible with live‐cell super‐resolution microscopy. (30th March 2020) - Pereira, Pedro M.; Gustafsson, Nils; Marsh, Mark; Mhlanga, Musa M.; Henriques, Ricardo
Abstract: Localization‐based super‐resolution microscopy relies on the detection of individual molecules cycling between fluorescent and non‐fluorescent states. These transitions are commonly regulated by high‐intensity illumination, imposing constrains to imaging hardware and producing sample photodamage. Here, we propose single‐molecule self‐quenching as a mechanism to generate spontaneous photoswitching. To demonstrate this principle, we developed a new class of DNA‐based open‐source super‐resolution probes named super‐beacons, with photoswitching kinetics that can be tuned structurally, thermally and chemically. The potential of these probes for live‐cell compatible super‐resolution microscopy without high‐illumination or toxic imaging buffers is revealed by imaging interferon inducible transmembrane proteins (IFITMs) at sub‐100 nm resolutions. Abstract : Live‐cell compatible illumination